Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1039/c2cp23775j
|View full text |Cite
|
Sign up to set email alerts
|

Nickel phosphide-embedded graphene as counter electrode for dye-sensitized solar cells

Abstract: Nickel phosphide-embedded graphene, prepared by the hydrothermal reaction of red phosphorus, nickel chloride, and graphene oxide in a mixture of ethylene glycol-water, is investigated as the counter electrode of DSSCs. It is demonstrated that the DSSC with the nickel phosphide-embedded graphene as the new counter electrode presents an excellent performance competing with that of the Pt electrode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
99
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(99 citation statements)
references
References 38 publications
0
99
0
Order By: Relevance
“…[7] Hence, cost-effective and highly electrocatalytic alternative CE materials should be developed. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Iron (Fe) widely exists in the Earth's crust and ranks fourth among the most abundant elements, following oxygen, silicon, and aluminum. Fe compounds with various compositions, valence states, and crystal structures [23,24] are abundant, cost effective, and environmentally friendly; furthermore, Fe compounds have been extensively investigated because of important optical, electrical, optoelectronic, and transport properties.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Hence, cost-effective and highly electrocatalytic alternative CE materials should be developed. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Iron (Fe) widely exists in the Earth's crust and ranks fourth among the most abundant elements, following oxygen, silicon, and aluminum. Fe compounds with various compositions, valence states, and crystal structures [23,24] are abundant, cost effective, and environmentally friendly; furthermore, Fe compounds have been extensively investigated because of important optical, electrical, optoelectronic, and transport properties.…”
Section: Introductionmentioning
confidence: 99%
“…These transition metal compounds also find other applications, e.g., super capacitors [17], fuel cells [18], and sensors [19]. Among these transition metal compounds, nickel based compounds, such as NiS, Ni 3 S 2 [9,20], Ni 12 P 5 [21], and sulfur-doped NiO [22], were proved to show superior electro-catalytic ability, when they were used as counter electrode materials in DSSCs. A nickel incorporated carbon nanotube/nanofiber composite CE rendered for its DSSC a solar-to-electricity conversion efficiency (Á) of 8.32%, which was much better than that of the DSSC (7.96%) with a platinum counter electrode (Pt-CE) [23].…”
Section: Introductionmentioning
confidence: 98%
“…Among the reported exploited doping elements, N atom and carbonaceous materials received particular attention to improve the performance in DSSCs [13,[17][18][19][20]. However, the corresponding concentration of the doping elements should be carefully adjusted as using large amount of these doping species can create carrier recombination centers or light-harvesting competition with dye which greatly minimizes the performances of photoelectrode [21][22][23][24]. Recently, experimental studies have demonstrated that low concentration co-doping of TiO 2 with both non metal-anions and metal-cations can enhance the efficiency of DSSCs compared with mono-doping [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%